Coconut Fiber Strengthen High Performance Concrete: Young’s Modulus, Ultrasonic Pulse Velocity and Ductility Properties - A. Othuman Mydin, M; Mohd Zamzani, N (International Journal of Engineering and Technology, 2018)
This paper emphasis on experimental investigation to govern the engineering properties such as young’s modulus, pundit ultrasonic pulse velocity (UPV) and ductility of High Performance Concrete (HPC) with grade M60 with addition of coconut fibre (CNF) together with silica fume (SF) and pulverised fuel ash (PFA). For this study, 3 mixes were prepared. First was the CNFRC without any additives, secondly the CNFRC made by 10% replacement of cement weight with PFA and thirdly composition of 10% of cement weight was exchanged with SF. It should be pointed out that for each mix; CNF was included in the mixture (0.5% of the mix volume). The investigational results had shown that the Young’s modulus of CNFRC, CNFR SFC and CNFR PFAC enhanced by about 6%, 3%, and 12% correspondingly. In terms of ductility, when control HPC specimens were subjected to axial compressive strength, slight preliminary cracks shaped on the surface of specimens. Among all HPC specimens tested, CNFR PFAC attained the utmost UPV at 28 day.